Sorafenib maintenance in FLT3-ITD mutated AML after allogeneic HCT: a real-world, single-center experience - Diral, Elisa; Furnari, Giulia; Bruno, Alessandro; Greco, Raffaella; Clerici, Daniela; Marktel, Sarah; Farina, Francesca; Mastaglio, Sara; Vago, Luca; Piemontese, Simona; Peccatori, Jacopo; Corti, Consuelo; et al. (Frontiers in Oncology, 2024)
Despite allogeneic hematopoietic stem cell transplant (allo-HCT) and the development of novel FLT3 inhibitors in both induction (midostaurin) and in the relapsed/refractory setting (gilteritinib), FLT3-ITD mutated leukemia (FLT3-ITD+ AML) still represents a challenge for modern hematology. Sorafenib is to this date the only inhibitor that demonstrated efficacy in improving both progression free and overall survival as post HCT maintenance therapy, even if its use in this setting has not been approved so far by regulatory agencies. The aim of our study was to evaluate the feasibility, safety and efficacy of sorafenib maintenance in preventing early relapse in FLT3-ITD+ AML after HCT in a single center experience. We analyzed 26 consecutive patients who received post HCT 2-year maintenance with sorafenib at our center between 2017 and 2023. Median time from HCT to sorafenib start was 130 days and median dosage was 200 mg per day. Two (8%) and three (12%) patients discontinued maintenance due to toxicity and disease relapse, respectively. 8 (31%) patients terminated the 2-year maintenance and stopped sorafenib, while 13 patients are still under treatment. Overall, 21/26 patients (81%) are alive and in stable complete remission as outlined by a 2 year disease free survival of 83.61%. No major long-term toxicity were reported at last follow up. Our real-world experience supports the use of sorafenib as a feasible and effective therapeutic option in post HCT maintenance for FLT3-ITD+ AML.